(untitled) (Research, Society and Development, 2021)
The high demand for healthy food is a relevant factor for the development of food products. In this sense, vegetables are rich in nutrients that give them functional properties. Therefore, the objective was to prepare a meat sauce, made of pineapple with pepper, and to evaluate its color and sensory acceptability. Three formulations were prepared with the same processing conditions and variation in the thickeners used (F1 - Xanthan Gum; F2 - Carragena Gum; F3 - Carboxymethylcellulose). The sauces were made by mixing the ingredients cold. Instrumental color parameters (L *, a *, b *, H °, C *) were evaluated with a Minolta CR400 colorimeter. The acceptance test of the attributes of aroma, color, flavor, consistency and global aspect was performed using a 9-point hedonic scale and the purchase intention test with a 5-point attitude scale, both with 80 consumers. The sauces showed yellow color, with greater luminosity (45.38) and intensity (39.55) of color observed in the sauce elaborated with Goma Carragena, while the greater hue (85.02) was perceived in the sauce produced with Goma Xantana. Sauces showed good acceptance for all attributes, with an acceptability index greater than 70%, except for the consistency of the sauce made with Goma Carragena (67%). There were no significant differences between the intention to purchase the samples (F1- 3.70; F2- 3.54; F3- 3.43). Therefore, the study demonstrates the importance of choosing a thickener for the preparation of sauces and the need to adapt the formulation prepared with Carragena Gum.